Tren Kecantikan dalam Perspektif Hadis - Muhammad Bilal Fauzi; Salim Rosyadi (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
Beauty trends are actions that can reflect the values or views that prevail in society regarding perceptions of beauty, this gives rise to a new culture that is followed by society. This article aims to provide the boundaries of moral values that are in accordance with Islamic sharia through a review of hadith. This research uses a contemporary hadith thematic method by applying the grounded theory method. There are 6 hadiths found from the Maktaba Shameela or the Hadith Book of 9 Imams. The hadiths found were narrated by Sahih Bukhari, Sahih Muslim, Sunan Tirmidhi, and Sunan Ahmad. This research concludes that beauty trends are permissible from a religious perspective, as long as the actions do not deviate from the sharia values taught in Islamic guidelines (Al-Quran and Hadith).